Selected Lectures of the Meeting “From the First Thousand Days to Aging: Life is a Continuum. Epigenetics, Artificial Intelligence and Environmental Impact”; Cagliari (Italy); October 25, 2024 - --- Various Authors (Journal of Pediatric and Neonatal Individualized Medicine)
Selected Lectures of the Meeting “From the First Thousand Days to Aging: Life is a Continuum. Epigenetics, Artificial Intelligence and Environmental Impact”; Cagliari (Italy); October 25th, 2024